Binding of CXCL8/IL-8 to Mycobacterium tuberculosis Modulates the Innate Immune Response - Agnieszka Krupa; Marek Fol; Bozena R. Dziadek; Ewa Kepka; Dominika Wojciechowska; Anna Brzostek; Agnieszka Torzewska; Jaroslaw Dziadek; Robert P. Baughman; David Griffith; Anna K. Kurdowska (Mediators of Inflammation)
Interleukin-8 (IL-8) has been implicated in the pathogenesis of several human respiratory diseases, including tuberculosis (TB). Importantly and in direct relevance to the objectives of this report quite a few findings suggest that the presence of IL-8 may be beneficial for the host. IL-8 may aid with mounting an adequate response during infection with Mycobacterium tuberculosis (M. tb); however, the underlying mechanism remains largely unknown. The major goal of our study was to investigate the contribution of IL-8 to the inflammatory processes that are typically elicited in patients with TB. We have shown for the first time that IL-8 can directly bind to tubercle bacilli. We have also demonstrated that association of IL-8 with M. tb molecules leads to the augmentation of the ability of leukocytes (neutrophils and macrophages) to phagocyte and kill these bacilli. In addition, we have shown that significant amount of IL-8 present in the blood of TB patients associates with erythrocytes. Finally, we have noted that IL-8 is the major chemokine responsible for recruiting T lymphocytes (CD3+, CD4+, and CD8+ T cells). In summary, our data suggest that the association of IL-8 with M. tb molecules may modify and possibly enhance the innate immune response in patients with TB.